Compensation Discrimination for Wide Receivers: Applying Quantile Regression to the National Football League - Burnett, Nancy J; Scyoc, Lee J. Van (Journal of Reviews on Global Economics, 2013)
Keefer's recent article in the Journal of Sports Economics (2013) finds evidence of wage discrimination in the National Football League (NFL) market for linebackers. We examine the market for NFL wide receivers using similar techniques as Keefer, though we explore only rookies rather than all current players and wide receivers rather than linebackers. While we would expect to find stronger evidence of discrimination in the rookie market, as rookies are captured sellers, we find no pervasive pattern of pay discrimination by race in this market.